EVALUATION OF DISTRICT COOPERATIVE BANKS IN KERALA: ON THE BASIS OF AGRICULTURAL CREDIT - Sanitha A.C. and Philo Francis
14 District Co-operative Banks are working under the guidance of Kerala State Cooperative Bank in Kerala. District Cooperative Banks are included in the short-term credit structure of cooperatives. DCBs offer only short term and medium term credit for agricultural and nonagricultural operations. Short term agricultural loans include: loans for seasonal agricultural operations, marketing of crops, selling and distribution of agricultural commodities etc. Medium term agricultural credit includes: minor irrigation, animal husbandry etc. the study found that, DCBs gave more importance to short-term agricultural credits than medium term agricultural credits, DCBs have a good capacity to collect the short term agricultural loans without losing more amount in overdues, and it has a capacity to reduce its NPA relating to agricultural credit in the future.